The Role of Lexical Metaphor and Grammatical Metaphor in the lbert Miller’s Poem: “The Ear is an Organ Made for Love” - Khattab, Maysoon Khaldoon (International Journal of Psychosocial Rehabilitation, 2020)
This paper offers an exploration for the textual role of i.) lexical metaphor (LM), and ii.) grammatical metaphor(GM) in the linguistic realization of one poem written by the contemporary black American poet: Ethelbert Miller. Such an exploration has been done by identifying, assessing, and comparing the textual function of these two different types of metaphor in the realization of semantic message and the aesthetic function in the data. Data analysis shows that this poetic text makes use of LMs and GMs, a fact indicating that both types of metaphor undertake a constitutive text-creation role. In this particular text, LMs are found in all the sentences of the poem, and they outnumber GMs. Hence LMs are more contributory to the semantic load of the text as a whole; and to the delivery of the poet’s message of lamenting the loss of hearing people everywhere speaking lovely language.